Meningkatkan Kompetensi Guru dalam Proses Pembelajaran Berdasarkan Kurikulum 2013 Melalui Supervisi Akademik di SD Negeri 40 Ampenan - Rusmiarsi, Rusmiarsi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2017)
The purpose of this study is to determine the effectiveness of the implementation of academic supervision in an effort to improve the competence of classroom teachers in learning in the classroom. This research was conducted in three cycles; each cycle activity consisted of stages namely planning, implementation, observation, and reflection. The indicators of success in this study are; 1) school principal observation result and teacher observation during mentoring process has got average score> 4.0, 2) the final result> 85% of the number of mentoring participants get average score> 80.00 (good category). The result of the research in cycle I the principal observation average score (2.80), teacher observation average score (3.00) and academic grade teacher supervision average score (61.35). In cycle II the result of principal observation average score in the target (3.50), teacher observation average score (4.00) and academic supervision result average score (78.73). In cycle III the principal observation average score (4.50), teacher observation average score (4.50) and academic supervision results average score in the target (86.25). The success indicator has been reached, the research is stated successful and stopped in cycle III.The result of research on the 3rd cycle shows improvement on teacher's competence in the learning process in the real class. It is recommended that other principals conduct similar research in an effort to increase the competence of class teachers in well-planned scenario andresponsibility, for improving learners’ learning achievement in accordance with the field of study / the lesson to whichthe teacher is responsible for.